Muslim Sellers’ Knowledge of Halal Cosmetics Awareness: Regression Analysis Approach - Jabar, Faizan Abd; Wahid, Sharifah Norhuda Syed; Ahmad, Mohamad Azmi Nias; Mohammed, Mohd Faizal Azrul Azwan; Azudin, Muhammad Zainuddin Mohamed; Manap, Nurma Abdul; Nordin, Mohd Norazmi (CENTRAL ASIA AND THE CAUCASUS, 2022)
Purpose - This article examines the Muslim Sellers' Knowledge of Halal Cosmetics Awareness. Muslims around the world are now directed on products that are halal, clean and safe to consume and this includes cosmetic products. Due to the increase in demand for halal cosmetics globally, existing and new players in the cosmetics industry are taking advantage of this situation and are competing to produce halal cosmetic products. As such, it is crucial to lay the responsibility of selling products that fulfil the sharia requirements on the cosmetic products sellers. Hence, the sellers need to have awareness and knowledge regarding the concept of halal and haram.Design/ methodology/ approach - This study employs survey technique to measure two variables comprised of sellers' knowledge, and awareness. The questionnaire items attempt to capture basic requirement for cosmetics products in conjunction with Malaysian consumers' rights. It is divided into two parts: Part A and Part B. Part A consisted of questions on the demographic background of the respondents. Meanwhile, Part B consisted of two sections which focused on knowledge (four items) and awareness (five items). Regression analysis was conducted to examine the proposed impact via IBM-SPSS AMOS 24. There are120 selected registered Muslim cosmetic sellers with at least one year of experience in the halal cosmetic industry from four different towns in one of the states on East Coast of Malaysia. They were involved in this study using a convenience sampling technique.Findings - The analysis indicates a significant positive effect of knowledge on awareness among Muslim cosmetics sellers. This result demonstrates that knowledge is a very important factor that influenced the awareness level towards halal cosmetics product.Research limitation/implication/contribution – This study is conducted on halal cosmetics sellers in selected towns in one state of the East Coast of Malaysia only. The usual limitations associated with self-reported questionnaires such as low response rate, response bias and non-response bias, apply. This study also may not be generalized to other countries which have different political, cultural and economic factors. There might be other variables that were excluded from this study making the model incomplete, and therefore care should be taken in interpreting and generalizing its findings. This study is essential for sellers to be informed be responsible towards customers and not seek profit-orientation solely. JAKIM, the agency of halal approval in collaboration with MOH (Ministry of Health) able to encourage the Muslims' sellers with provide many related activities to upgrade their knowledge as well as their awareness regarding destructive products, responsibility towards their stakeholders and religion. They also should be firm with the enforcement and penalties for those who break the laws in eradicating cosmetics that are destructive and non-compliant with Shariah.Originality/value - Therefore, it is highly recommended that authorized agencies such as JAKIM initiate more activities to create awareness among Muslim sellers on the concept of halal for consumers' benefits.